Exploring the Nuanced Links Between Internet Use and Subjective Well-Being Among Older Adults: A Nordic Population-Based Study - Viklund, Emilia W. E.; Forsman, Anna K. (Frontiers in Psychology, 2022)
Aim The aim was to explore the various associations between subjective well-being and internet use among older adults in two regions in Finland and Sweden. Methods The data was collected through a population-based survey (N = 9,386) as part of the GERDA project conducted in 2016. The connection between subjective well-being (measured by perceived meaningfulness, happiness and life satisfaction) and internet use (distinguishing between internet users, non-users and users with support, and diverse internet activities) was studied by conducting binary regression analyses, calculating odds ratios with 95% confidence intervals. The analyses also controlled for key subjective well-being covariates. Results Statistically significant associations were found between perceived life meaningfulness and internet use. When looking into the specific internet-based activities under study, activities related to leisure and entertainment showed statistically significant associations to perceived meaningfulness as well as perceived happiness, also after controlling for potential covariates. However, internet use and the different internet activities failed to show statistical significant associations to life satisfaction in the adjusted regression model. Conclusion The things we do on the internet (the activities) as well as how we conceptualize and measure subjective well-being in this type of research studies seem to matter when it comes to the relationship between subjective well-being and internet use in later life. Internet use and internet activities displayed various connections to the subjective well-being proxies used in this study. Therefore, the complexity and multidimensionality of both subjective well-being and internet use and related links need to be carefully explored in order to deepen our understanding of experienced well-being among older adults in a digitized world.